Outcomes of Eyelid Malignant Tumor Patients at Wahidin Sudirohusodo Hospital: Oral Presentation - Observational Study - Resident - DESTI PRIANI; Dr. dr. Halimah Pagarra, Sp.M(K); dr. Ahmad Ashraf Amalius, MPH, Sp.M(K), M.Kes; dr. Andi Pratiwi, Sp.M, M.Kes (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The prevalence of malignant eyelid tumors varies, 80–95% are basal cell carcinomas (BCC), 5% are squamous cell carcinomas (SCC), and 1–3% are sebaceous gland carcinomas (SGC), and most of them are removed by complete resection. However, recurrence, metastasis, and tumor expansion are still common in these cases. This study aims to assess the characteristics and outcomes of eyelid malignant tumor patients at Wahidin Sudirohusodo Hospital. Methods : This study used a retrospective cohort and was conducted using secondary data from medical records for five years at Wahidin Sudirohusodo Hospital. Data on general characteristics, clinical characteristics, and outcomes were collected, then analyzed and presented in tabular form. Results : From 44 samples, females made up 75.0% and the largest age group was 45–64 years (65.9%). The tumor was most commonly located in the right eye (61.4%) and the superior eyelid (50.0%), with an onset of 36.36±37.75 months. BCC was the most frequent tumor (61.3%), especially nodular (81.5%). During the follow-up, recurrence (25%) was most prevalent in BCC (63.6%; p: 0.976), with an average recurrence of 31.36±32.47 months (p: 0.894). Metastases (2.3%) occurred in 1 SCC patient after 12 months, and tumor expansion (2.3%) occurred in 1 SGC patient. Conclusion : There was no difference in the incidence of tumor recurrence, metastasis, and expansion based on tumor type and location. However, there was a significant difference in the type of management taken against the tumor expansion. Follow-up must be done for at least three years after therapy.